2019
DOI: 10.5433/1679-0359.2019v40n3p1049
|View full text |Cite
|
Sign up to set email alerts
|

Budburst and flowering intensity by the spraying of dormancy-breaking products in ‘Eva’ apple trees

Abstract: Spraying of dormancy-breaking chemicals is a mandatory procedure to produce temperate fruits in low-chill regions. Although hydrogen cyanamide (HC) + mineral oil (MO) show efficiency enhancing budburst, the usage of HC is restricted in some countries due to its toxicity. Therefore, this research aimed to evaluate the efficiency of spraying different dormancy-breaking agents on ‘Eva’ apple tree buds, under the conditions of the Depressão Central of Rio Grande do Sul, Brazil. Different doses of Erger® (0, 2, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As a consequence, growers traditionally applied pesticides lib-erally, spraying to the point of runoff to ensure sufficient control of pests that have the potential to devastate crops, including those pests for which a small amount of damage can result in significant economic losses. This practice is still common despite some modern pesticide labels recommending lower spray volume application rates (Darde et al, 2019;Lordan et al, 2019;Walklate et al, 2003). Moreover, in crops where there are dense canopies or multirow production blocks, such as orchards and nurseries, large volumes of spray solution are applied by airassisted sprayers to ensure adequate spray deposition in the interior of the canopy, regardless of whether the tree is positioned in an exterior or interior row (Zhu et al, 2017).…”
mentioning
confidence: 99%
“…As a consequence, growers traditionally applied pesticides lib-erally, spraying to the point of runoff to ensure sufficient control of pests that have the potential to devastate crops, including those pests for which a small amount of damage can result in significant economic losses. This practice is still common despite some modern pesticide labels recommending lower spray volume application rates (Darde et al, 2019;Lordan et al, 2019;Walklate et al, 2003). Moreover, in crops where there are dense canopies or multirow production blocks, such as orchards and nurseries, large volumes of spray solution are applied by airassisted sprayers to ensure adequate spray deposition in the interior of the canopy, regardless of whether the tree is positioned in an exterior or interior row (Zhu et al, 2017).…”
mentioning
confidence: 99%
“…Campoy et al ( 2011) observed advanced blooming and harvest times for 'Early Maycrest' peach plants when they were treated with HC in combination with mineral oil [34]. Similarly, the application of 0.6% HC in combination with 4% mineral oil to 'Eva' apple trees can also effectively promote earlier vegetative and reproductive bud break [6]. In our study, application of HC alone or in combination with GA 3 , mineral oil, and KNO 3 , as well as ethephon promoted budbreak and fruit ripening in highbush blueberry (Table 2), and there is no clear difference in the effect on advancing budbreak and fruit ripening among different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Some chemical products, such as gibberellins (GA) [4], cytokinins [5], mineral oil (MO) [6], and potassium nitrate (KNO 3 ) [7] have been shown to exert a positive effect on the release of dormancy and thus on bud break when applied at the right concentration to the buds of many fruit crops. Hydrogen cyanamide (HC) is the most effective of a range of chemicals used to advance and synchronize bud break, promote early ripening, and increase fruit productivity in deciduous fruit trees [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations